A virtual university for small states of the Commonwealth (Commonwealth of Learning VancoverUS, 2003)
Looks at the current state of higher education in the regions of the small states. Considers the emerging models of virtual education and the applications of information and communications technologies in education. Presents a proposal.
Additional copy located in the Office of the Secretary-General